PENGEMBANGAN MEDIA PEMBELAJARAN BERBASIS GUIDED READING UNTUK MENINGKATKAN KEMAMPUAN MEMBACA KRITIS SISWA KELAS IV SD - Maani Maani; A. Gafar Hidayat; Nurul Uyun; Ita Fitriati (EDUCATIONAL : Jurnal Inovasi Pendidikan & Pengajaran, 2026)
ABSTRACT Critical reading ability is an essential skill that needs to be developed among elementary school students to support their capacity to comprehend, analyze, and evaluate information in depth. However, the learning process in schools still requires instructional media that can effectively facilitate the development of this skill. Therefore, this study aimed to develop guided reading-based learning media to improve the critical reading ability of fourth-grade elementary school students. This study employed the ADDIE development model, which consists of the analysis, design, development, implementation, and evaluation stages. The participants were 24 fourth-grade students. The research instruments included validation sheets, practicality questionnaires, and a critical reading ability test. The results indicated that the developed learning media met the criteria of validity, practicality, and effectiveness. The practicality of the media obtained a percentage score of 80.4%, while its effectiveness was demonstrated by an increase in students’ critical reading ability, with an N-Gain score of 0.61 (moderate category) and hypothesis testing results showing a significant effect (p < 0.05). Therefore, the guided reading-based learning media is considered feasible for improving elementary school students’ critical reading ability. ABSTRAK Kemampuan membaca kritis merupakan salah satu keterampilan penting yang perlu dikembangkan pada siswa sekolah dasar untuk mendukung kemampuan memahami, menganalisis, dan mengevaluasi informasi secara mendalam. Namun, proses pembelajaran di sekolah masih memerlukan media yang mampu memfasilitasi pengembangan kemampuan tersebut secara optimal. Oleh karena itu, penelitian ini bertujuan untuk mengembangkan media pembelajaran berbasis guided reading dalam meningkatkan kemampuan membaca kritis siswa kelas IV sekolah dasar. Penelitian ini menggunakan model pengembangan ADDIE yang meliputi tahap analisis, desain, pengembangan, implementasi, dan evaluasi. Subjek penelitian berjumlah 24 siswa. Instrumen penelitian meliputi lembar validasi, angket kepraktisan, dan tes kemampuan membaca kritis. Hasil penelitian menunjukkan bahwa media pembelajaran yang dikembangkan memenuhi kriteria valid, praktis, dan efektif. Kepraktisan media memperoleh persentase sebesar 80,4%, sedangkan efektivitas media ditunjukkan oleh peningkatan kemampuan membaca kritis siswa dengan nilai N-Gain sebesar 0,61 (kategori sedang) serta hasil uji hipotesis yang menunjukkan pengaruh signifikan (p < 0,05). Dengan demikian, media pembelajaran berbasis guided reading layak digunakan untuk meningkatkan kemampuan membaca kritis siswa sekolah dasar.